The African Continental Free Trade Area: Perspectives for Africa, policy choices for Europe - Evita Schmieg (Stiftung Wissenschaft und Politik (SWP), 2020)
The Agreement Establishing the African Continental Free Trade Area (AfCFTA) came into force in May 2019. Ultimately the AfCFTA is designed to create a comprehensive African market; what is does at this stage is set in motion a set of complex and foreseeably very lengthy negotiations. The outcome of that process will not yet be full free trade in Africa, but it will bring about a reduction in tariffs with the potential to stimulate production and trade and boost regional value chains. It is, however, too early to be discussing modifying the European Union's trade policy towards Africa, or for this to be an issue for the upcoming German Council Presidency. Nevertheless, Germany and the European Union should continue to follow and support the process of establishing the AfCFTA, which is an important political process with significant long-term economic potential for Africa.
Keywords: 320